Improving Students' Visualization Concept through Augmented Reality Textbook in the Animal Respiratory System Material - Nunung Nindigraha; Deka Dyah Utami; Ainir Rachmawati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This research and development aims to produce a feasible textbook with Augmented Reality on the topic of respiratory organs in animals. Research and Development (R&D) is a research method that results in a product. The development method used refers to the Sadiman model. In its implementation, the textbook with Augmented Reality serves as a supplementary tool in the learning process, meaning this product is designed to complement teaching the topic of respiratory organs in animals. The results of the product feasibility tests conducted with media experts and subject matter experts, as well as field trials with students, show that the Augmented Reality product received positive responses, is feasible, and can be used in the learning process. Thus, it can be concluded that the Augmented Reality textbook can serve as a supplementary resource for students learning about animal respiratory organs, as its use can facilitate, motivate, and increase students' interest in the subject.